Settlement Of Cross-Border Sharia Economic Disputes Through Arbitration Forum - Helza Nova Lita (Faculty of Shariah and Law, UIN Syarif Hidayatullah Jakarta, 2022)
In the practice of national and international business contracts, the parties can choose the forum and choice of law that will be used if there is a dispute that occurs in the implementation of the contract. In the resolution of international business disputes, the choice of law chosen can use one of the material law provisions of a particular country, while the choice of forum can choose a particular institution such as the Court, arbitration or other dispute resolution institutions. In practice, the choice of forum for settlement through arbitration is widely used because it is relatively easy and fast. Arbitration institutions are generally used in the resolution of international business disputes. In this article, we will study further about the role of arbitration in the settlement of sharia economic disputes that cross national borders. This is certainly interesting to study because it is related to sharia aspects as well as national and international regulations. The analytical method used is normative juridical, with reference to the provisions of aspects of Islamic law, national law, and international law. In Islamic law, every form of agreement must be obeyed by the parties who make it as long as it does not conflict with sharia principles. In International Civil Law, there is a Choice of Law and Choice of Forum in the resolution of international business disputes. This can also be used by the parties to choose a sharia arbitration forum as a dispute resolution institution in their business which is stated in the contract clauses they have agreed to. Recognition of the implementation of foreign arbitral awards must first have an agreement between countries and the decision does not conflict with public order and the legal provisions of the country where the implementation of the arbitral award is implemented. Keywords: arbitration, cross-border, Sharia.